Long term ophthalmic complications of distal arthrogryposis type 5D. (2nd January 2023) - Cohen, Dana; Sloma, Ronen; Pizem, Hadas; Fedida, Ayalla; Kalfon, Limor; Ovadia, Relli; Segal, Zvi; Kassif, Yanir; Falik Zaccai, Tzippi
ABSTRACT: Background: Distal Arthrogryposis type 5D (DA5D) is a rare genetic disease, expressed phenotypically by skeletal and ocular abnormalities. Materials and methods: Two sisters, ages 42 and 46 years old, were ascertained, both diagnosed with arthrogryposis and unusual ophthalmic late expressions of the disease. They were examined and followed up by both ophthalmologists and medical geneticists. Molecular analysis was performed and population screening followed among healthy individuals of the same ethnic background who reside in the same village. Results: The two sisters expressed myogenic ptosis with poor levator palpebrae function, limitation in up gaze, lagophthalmos, refractive errors, corneal scarring and vascularization along with severe distal arthrogryposis. The newly reported features were: significant lower lid retraction, causing inferior scleral show. Sanger sequencing of the coding regions of ECEL1 gene revealed a homozygous deletion of 46 bps. The carrier frequency is 1:24 (4.2% carriers) in the probands' village. Conclusions: We diagnosed two patients with DA5D carrying a homozygous pathogenic genetic variant previously reported only once. We report the late ophthalmologic manifestations of this rare disorder and emphasize the importance to recognize possible long-term ophthalmic complications. Measures are needed to diagnose this rare disorder at a younger age and to address ophthalmic and orthopedic complications that might be prevented. We revealed the causative genetic variant and a carrier frequency of 1:24 for DA5D, in the probands' village, thus enabling accurate genetic counselling and justifying genetic testing to the residents of this village as a diagnostic and preventive measure.